Analisis Framing Robert N. Entmant Pada Pemberitaan Ganjar Pranowo Di CNN Indonesia (Penolakan Timnas Israel Untuk Bertanding di Indonesia) - Bhagaskara Bintang; Andrine Prima Afneta Arzil (Jurnal Komunikasi Massa, 2024)
In March 2023, Ganjar Pranowo issued a statement rejecting the Israeli national team from competing in Indonesia at the FIFA U-20 event which was held in Indonesia. This statement certainly caused various responses from the public. This refusal is not merely a rejection but wants to maintain the mandate of Ir. Sukarno. In its distribution, online media has become the public's choice for seeking information related to the statement made by Ganjar Pranowo. The online media cnnindonesia.com is one of them, cnnindonesia.com is an international online news platform which finally opened a channel in Indonesia under the auspices of the transmedia group. This research aims to determine the framing carried out by cnnindonesia.com regarding the rejection made by Ganjar Pranowo regarding the Israeli National Team's participation in competing in Indonesia in the FIFA U-20 event using Robert N. Entman's framing analysis. This research uses a qualitative approach with Robert N. Enmant's framing model analysis. The elements used in this model consist of Define Problems, Diagnose causes, Make Moral Judgment, Treatment Recommendation. The object of this research uses news released from March 24 2023 to April 5 2023, a total of 9 news items. The results of this research show that cnnindonesia.com was initially a place for clarification, but after FIFA canceled the event where Indonesia was the host, cnnindonesia.com wrote that one of the reasons the event was canceled was because of the rejection by Ganjar Pranowo.